Overview of Obstetric Fistula: From a Developing Country’s Perspective - Dangal, Ganesh; Bajracharya, Nishma; Karki, Aruna; Pradhan, Hema; Shrestha, Ranjana; Bhattachan, Kabin (Journal of Nepal Health Research Council, 2020)
Obstetric fistula is a hidden tragedy in the developing world, prevention is important and treatment is by surgical repair. However, failure, broken fistula, stress incontinence often demoralizes surgeons and patients.Keywords: Fistula repair; Obstetric fistula; Obstructed delivery.